Взаимоотношения нервных клеток, капилляров и глин в некоторых отделах коры головного мозга кошки (Felis domestica) и кролика (Oryctolagus cuniculus) - Гитилис, В.С.; Савицкая, Л.Г. (Вестник зоологии, 1977)
The degree of nerve cells vascularization, quantitative, spatial relations of capillaries, glia and different types of neurons in motor and somatosensory zones of the cerebral cortex in Felis domestica and Oryctolagus cuniculus are determined by morpho-functional peculiarities of the animals. The optimal zone of vascularization is within a radius of 5-15 gm from the cell body. Distribution of glial cells is different for various types of nerve cells in the vascularization zone.